Impact of bullying victimization on suicide and negative health behaviors among adolescents in Latin America - Matthew L. Romo; Elizabeth A. Kelvin
ABSTRACT Objective To compare the prevalence of bullying victimization, suicidal ideation, suicidal attempts, and negative health behaviors (current tobacco use, recent heavy alcohol use, truancy, involvement in physical fighting, and unprotected sexual intercourse) in five different Latin American countries and determine the association of bullying victimization with these outcomes, exploring both bullying type and frequency. Methods Study data were from Global School-based Student Health Surveys from Bolivia, Costa Rica, Honduras, Peru, and Uruguay, which covered nationally representative samples of school-going adolescents. The surveys used a two-stage clustered sample design, sampling schools and then classrooms. Logistic regression models were run to determine the statistical significance of associations with bullying. Results Among the 14 560 school-going adolescents included in this study, the prevalence of any bullying victimization in the past 30 days was 37.8%. Bullying victimization was associated with greater odds of suicidal ideation with planning (adjusted odds ratio (AOR): 3.12; P < 0.0001) and at least one suicide attempt (AOR: 3.07; P < 0.0001). An increasing exposure-response effect of increasing days of bullying victimization on suicide outcomes was also observed. Bullying victimization was associated with higher odds of current tobacco use (AOR: 2.14; P < 0.0001); truancy (AOR: 1.76; P < 0.0001); physical fighting (AOR: 2.40; P < 0.0001); and unprotected sexual intercourse (AOR: 1.77; P < 0.0001). Conclusions Although the prevalence of bullying victimization varied by country, its association with suicidal ideation and behavior and negative health behaviors remained relatively consistent. Addressing bullying needs to be made a priority in Latin America, and an integrated approach that also includes mental and physical health promotion is needed.